Learning from nature: Exploring systems of plants and animals for form generation - Arnis Rochma Harani (Department of Architecture Faculty of Engineering Universitas Indonesia, 2023)
This paper aims to explain learning strategies for deconstructing and reconstructing natural objects as hidden knowledge in nature for application in design studio pedagogy, particularly in developing architectural forms. Current discourse on nature-based architecture learning often places nature as a form of metaphor and analogy. This article presents various results of tracing natural systems, especially plants and animals, as a basis for learning architecture in the Basic Design studio at the Department of Architecture, Faculty of Engineering, Universitas Diponegoro. The implementation of the design studio was conducted by groups of students who explore different types of plant and animal objects. The students were assigned to explore all the interesting aspects of the selected object's system in order to gain specific knowledge beyond the physical. The studio outputs demonstrate an exploration of new architectural forms based on the hidden knowledge of nature. The exploration method of this study follows the pedagogical process in the studio with data collection being carried out periodically through direct observation during model-making time. The learning result of this studio triggers students to be aware of the various hidden knowledge in the environment that can be used as a basic system for developing architectural forms.